Improving patient care : the implementation of change in health care - Grol, Richard; Wensing, Michel; Eccles, Martin; Davis, David (Chichester, West Sussex : Wiley-Blackwell/BMJ Books, 2013)
As innovations are constantly being developed within health care, it can be difficult both to select appropriate new practices and technologies and to successfully adopt them within complex organizations. It is necessary to understand the consequences of introducing change, how to best implement new procedures and techniques, how to evaluate success and to improve the quality of patient care. This comprehensive guide allows you to do just that. Improving Patient Care, 2nd edition provides a structure for professionals and change agents to implement better practices in health care.
3.4. Assessment of performance3.5. Analysis of the target group and setting; Aims and settings of the implementation; Segments within the target group and stages of change; Phases in a process of change: a summary of the literature; Barriers and facilitators to changing practice; 3.6. Development or selection of improvement strategies; 3.7. Development, testing, and execution of an implementation plan; 3.8. Sustainable change: integration of change into practice routines; 3.9. Evaluation and (possible) adaptations to the plan; 3.10. Planning of the implementation process; 3.11. Conclusions.
5.2. Various types of improvements require various types of change proposals.
ReferencesCHAPTER 4: Planning and organizing the change process; 4.1. Introduction; 4.2. A motivated team comprising all relevant expertise; 4.3. Creating a context for change; The central role of physicians; Collaboration in teams for patient care; 4.4. Involving the target group in the plan; 4.5. Leaders and key figures; Medical leadership; 4.6. Project management: time schedule and responsibilities; 4.7. Resources and support; 4.8. Conclusions; References; PART II: Guidelines and Innovations; CHAPTER 5: Characteristics of successful innovations; 5.1. Introduction.
Online resource; title from PDF title page (Wiley, viewed July 23, 2013).
Keywords: Health care reform; Patient Care; Health Care Reform; Quality of Health Care; Medicine; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Alternative Medicine; MEDICAL -- Atlases; MEDICAL -- Essays; MEDICAL -- Family & General Practice; MEDICAL -- Holistic Medicine; MEDICAL -- Osteopathy; Health care reform; Electronic books; Electronic books